Pengaruh Stres Kerja dan Keadilan Organisasi Terhadap Kinerja Tenaga Penjualan - Wulandari, Wulandari; Putra, Arif Rachman (TIN: Terapan Informatika Nusantara, 2024)
This study aims to analyze the effect of job stress and organizational justice on sales force performance. Work stress is based on the workload and time experienced while organizational justice reflects salespeople's perceptions of the evaluation and treatment received. This study uses a quantitative approach with 100 smartphone salespeople in the Surabaya City Region who are still active as samples. The results showed that job stress experienced by salespeople had a significant downward effect on sales force performance. Organizational justice received has a significant effect on sales force performance. The implications of this study focus on the importance of the level of competition, the nature of the job, and the work environment to reduce the impact of stress. Organizations can start paying attention to the feedback provided by transparent evaluation, non-discriminatory treatment, and consideration of remuneration for salespeople. The results of this study provide insight into the factors that influence the decline and improvement of sales force performance in terms of job stress and organizational justice.